2012
DOI: 10.1186/2044-7248-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Subtle changes in the flavour and texture of a drink enhance expectations of satiety

Abstract: Background: The consumption of liquid calories has been implicated in the development of obesity and weight gain. Energy-containing drinks are often reported to have a weak satiety value: one explanation for this is that because of their fluid texture they are not expected to have much nutritional value. It is important to consider what features of these drinks can be manipulated to enhance their expected satiety value. Two studies investigated the perception of subtle changes in a drink's viscosity, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 53 publications
7
38
0
Order By: Relevance
“…This is in accord with studies which show that texture has a large effect on satiety expectations (e.g. 26,27). In addition, the association between dairy and energy is already learned during infancy which is the most sensitive period for learning associations between sensory signals and metabolic consequences [28].…”
Section: Discussionsupporting
confidence: 91%
“…This is in accord with studies which show that texture has a large effect on satiety expectations (e.g. 26,27). In addition, the association between dairy and energy is already learned during infancy which is the most sensitive period for learning associations between sensory signals and metabolic consequences [28].…”
Section: Discussionsupporting
confidence: 91%
“…The hypothesis put forward here is that sensation from the oral phase, through associative learning, triggers feelings of satiety rather than simply relying on signals from the stomach or small intestines. Indeed McCrickerd et al have shown that upon seeing drinks of different thickness (ranging in viscosity from 10–317 mPa.s at shear rate 50 sec -1 ) that participants expected to feel more full from ingesting the thicker drinks [53]. It has been hypothesised that textural qualities such as thickness provide cues as to the energy load within the drink.…”
Section: Reviewmentioning
confidence: 99%
“…For example, subtle changes to the viscosity of a yogurt drink generate reliable changes in expected satiety. 46 Similarly, people clearly discriminate between different types of desserts 47 and soups 48 based on their expected satiation.…”
Section: Expected Satiety Palatability and Self-selected Food Portionsmentioning
confidence: 99%